Light - Walpole, Brenda; Bull, Peter 1960-.; Chen, Kuo Kang. (London Kingfisher Books, 1987)
Presents experiments demonstrating such aspects of light as shadows, reflection, refraction, lenses, optical illusions, and color.
Keywords: Light -- Juvenile literature; Experiments; Light -- Experiments -- Juvenile literature; Light -- Experiments